Developing a nexus systems thinking test –A qualitative multi- and mixed methods analysis. (March 2021) - Schlör, Holger; Märker, Carolin; Venghaus, Sandra
Abstract: The most pressing global challenges have been summarized in the UN Sustainable Development Goals. Given the complex feedbacks and interdependencies among them, fulfilling these goals requires a holistic approach leading to profound transitions. The food-energy-water nexus is often proposed to be one such holistic approach. However, to date no consistent definition of the nexus concept exists, while research interest in the nexus rapidly grows. Therefore, in this paper, the nexus is defined as a concept of systems thinking. A nexus systems thinking test is developed that can be used as a new way of categorizing nexus research. To examine the test's viability and suitability, it is applied to a sample data set of nexus-related research papers. By means of a multi- and mixed methods document analysis it is analyzed if the papers conceptualize the nexus approach as a systems thinking concept. The results show that all papers meet the four system criteria. Different emphasis, however, is put on certain aspects. The nexus systems thinking test proved to be a viable systematic method to investigate if and in which way nexus research incorporates a systems thinking perspective. It does not only offer a new way of categorizing nexus related research, but also allows assessing its quality from a comprehensive nexus perspective. The test thus provides valuable and systematic understanding of a rapidly developing, central research field within sustainability science. Highlights: In this paper the nexus is conceptualized as a concept of systems thinking. A nexus systems thinking test is developed to review nexus research. The test adds a new review method to those published so far. A qualitative multi- and mixed methods approach is used for the analysis. All analyzed articles meet the system criteria but differ in their focus.